2018
DOI: 10.1001/jamanetworkopen.2018.4511
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Use of Therapeutic Hypothermia for Out-of-Hospital Cardiac Arrest

Abstract: Importance Despite evidence that therapeutic hypothermia improves patient outcomes for out-of-hospital cardiac arrest, use of this therapy remains low. Objective To determine whether the use of therapeutic hypothermia and patient outcomes have changed after publication of the Targeted Temperature Management trial on December 5, 2013, which supported more lenient temperature management for out-of-hospital cardiac arrest. Design, Setting, and Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 26 publications
1
40
1
5
Order By: Relevance
“…The existence of an association between changes in TTM policies and outcome is debated as previous authors reported conflicting results [20,21]. Our results are in accordance with those from a recent North-American study [8], which explored a quite similar population of post-cardiac arrest patients. On the opposite, our results are discordant with those from Salter et al [5], who reported an association between the progressive switch from 33 to 36°C and an increase in both the proportion with fever in ICU and hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The existence of an association between changes in TTM policies and outcome is debated as previous authors reported conflicting results [20,21]. Our results are in accordance with those from a recent North-American study [8], which explored a quite similar population of post-cardiac arrest patients. On the opposite, our results are discordant with those from Salter et al [5], who reported an association between the progressive switch from 33 to 36°C and an increase in both the proportion with fever in ICU and hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent retrospective study performed in Australia and New Zealand, similar changes in clinicians' attitude regarding target temperature after CA, which occurred in up to one third of ICU, were associated with an increased proportion of patients with fever [5]. In the USA, where this treatment was historically less employed as compared with European countries, TTM use was shown to further decrease in many centers, as revealed by recent administrative data [8]. In parallel, Khera et al found that TTM use dropped in all subgroups of CA survivors (both shockable and non-shockable) [9].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies indicate that clinical-induction of hypothermia can improve the neurological function of unconscious subjects following unexpected cardiac arrest by preserving heart and brain stability (50)(51)(52)(53). Recently, it has been reported that early application of mild hypothermia therapy not only improves the neurological outcome, but also increases the survival probability of patients postdischarge (54). The present study's findings indicated that higenamine and its regulated pathways could play a significant role in the mild hypothermia therapy.…”
Section: Discussionmentioning
confidence: 53%
“…A vizsgálat eredménye nagy vihart kavart a PCAS kezelésében, sok centrum szinte azonnal áttért a THTról a 36 °C-os testhőmérséklet-tartásra, mely az összes fiziológiai szervezeti választ és mellékhatást "kiveszi" a monitorozandó és kezelendő változók közül. A hűtési eljárás gyakorlatának csökkenése 2013 óta több vizsgálattal, regiszterrel alátámasztottan folyamatos, még az igen fejlett intenzív terápiás lehetőségekkel bíró országokban is (CARESS, ROC) [17]. Mindemellett úgy tűnik, hogy ezzel együtt a mortalitás enyhe emelkedést mutathat, mivel a 36 °C-os csoportokban több a hyperthermiás kiugrás, ami ugyanúgy káros a központi idegrendszernek, mint a THT leállításakor észlelt hyperpyrexia, amit a 2002-es tanulmányokban igazoltak.…”
Section: Célhőmérséklet-orientált Terápia a Pcas Kezelésébenunclassified